Validation of a FFQ (Food Frequency Questionaire) for older people - Corrente, José Eduardo [UNESP]; Marchioni, Dirce Maria Lobo; Fisberg, Regina Mara (My University, 2013)
Nutrition data for older adults is an area that has few studies mainly in Brazil. Due to the importance to know the behavior of this age group, the aim of this study was to develop and validate a frequency food questionnaire (FFQ) for older people in Brazil. It was considered a sample of 73 subjects from the city of Avaré, São Paulo, Brazil, and it was applied three 24-hour recalls and a FFQ developed for adults. Data from the three 24-hour recalls were transformed in nutrient intake as well as the data from FFQ. Statistical analysis was performed in order to get correlations between data from the mean of three 24-hour recalls and FFQ for some nutrients. It was found high correlations among them, concluding that the FFQ is valid to get nutrient intakes for older people.
Keywords: Older people; Food frequency questionnaire; Correlations; Nutrient intake